2022
DOI: 10.3389/fped.2022.1022743
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing ventilator support in severe bronchopulmonary dysplasia in the absence of conclusive evidence

Abstract: Given that there is no conclusive evidence for how to manage infants with severe BPD we have based our approach on the best available information relating to the respiratory physiology and expected natural history of the disease process. Ventilator managementThe best available evidence suggests that severe BPD is a heterogeneous lung disease that can be adequately described Miller et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…weeks PMA and has failed multiple extubation attempts. 46 Children needing tracheostomy and those with bronchopulmonary dysplasia with pulmonary hypertension have significant mortality. 10,47 ATS has published a guideline to support ventilation settings for those on home ventilation via tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…weeks PMA and has failed multiple extubation attempts. 46 Children needing tracheostomy and those with bronchopulmonary dysplasia with pulmonary hypertension have significant mortality. 10,47 ATS has published a guideline to support ventilation settings for those on home ventilation via tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…There is widespread variation in this practice and Murphy et al, reported that the center itself is the most distinctive factor in initiating home tracheostomy ventilation 45 . Audrey et al, recommended that tracheostomy may be attempted on the neonatal unit after an infant reaches the age of 52 weeks PMA and has failed multiple extubation attempts 46 . Children needing tracheostomy and those with bronchopulmonary dysplasia with pulmonary hypertension have significant mortality 10,47 .…”
Section: Discussionmentioning
confidence: 99%
“…16 Rapid ventilator weaning can result in atelectasis, worsening gas exchange, escalating FiO 2 requirements, and increased work of breathing. 29 The optimal timing and indications for tracheostomy are not known but the most common indications for tracheostomy are airway pathology and need for ventilation. 30…”
Section: Inpatient Managementmentioning
confidence: 99%
“…Infants with established severe BPD and heterogenous lung disease require a change in ventilation strategy to a slower rate, higher iT, high TV, and adequate PEEP, which often requires careful titration if severe airway malacia is present 16 . Rapid ventilator weaning can result in atelectasis, worsening gas exchange, escalating FiO 2 requirements, and increased work of breathing 29 . The optimal timing and indications for tracheostomy are not known but the most common indications for tracheostomy are airway pathology and need for ventilation 30 …”
Section: Bronchopulmonary Dysplasiamentioning
confidence: 99%
“…The timing of tracheostomy placement often involves waiting for multiple failed attempts at weaning from mechanical ventilation [ 12 , 44 ]. The notion that “we should try one more time” often underlies this and is a deliberate attempt to avoid tracheostomy given the risks for mortality and morbidity as well as the implications for parents and caregivers of a technology dependent infant.…”
Section: Tracheostomy Decision Makingmentioning
confidence: 99%